EXPLORATION OF ACCOUNTING STANDARDS IN BATIK TASIKMALAYA MSMEs IN EFFORTS TO IMPROVE BANKING CAPITAL ACCESS - Irfan Faris Rudiana; Dede Abdul Rozak; Roni Marsiana Suhendi (Jurnal Wawasan dan Riset Akuntansi, 2019)
The preparation of financial statements is one of the problems that is often overlooked by the business of Micro, Small and Medium Enterprises (MSMEs). Most MSMEs have not yet applied applicable financial accounting standards. The initial survey that has been conducted, found that most of the Batik Tasikmalaya MSMEs actors do not understand and apply the Standar Entitas Mikro Kecil dan Menengah (SAK EMKM) which are effective as of January 1, 2018, as a guideline in preparing the MSMEs financial statements to improve access banking capital. The purpose of this research is to analyze and find out the Application of Financial Accounting Standards in Preparing the Batik Tasikmalaya MSMEs Financial Report. This research uses a descriptive method with a quantitative approach. This study tested as many as 30 Batik MSMEs in Tasikmalaya is a sample. The results of the study showed that the financial statements prepared by MSMEs of Batik Tasikmalaya did not meet financial accounting standards.